1964
DOI: 10.2134/agronj1964.00021962005600050010x
|View full text |Cite
|
Sign up to set email alerts
|

Preemergence Control of Annual Bluegrass (Poa annua L.)1

Abstract: Synopsis Dacthal at 10 pounds, betasan at 15 pounds, dipropalin at 6 pounds, trifluralin at 2 pounds, and enide at 4 pounds per acre significantly controlled annual bluegrass for periods of 9 to 12 weeks. Dacthal and betasan were completely nonphytotoxic to mature turf. It is possible under field conditions to achieve good preemergence control of annual bluegrass if applications of these preemergence herbicides are made to coincide with the germination periods of the seed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

1966
1966
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Creeping bentgrass (CBG) is the cool-season turfgrass species of choice for golf course fairways and tees throughout the cool-humid region because it tolerates close mowing, remains green year-round, and possesses lateral stems that enable it to self-heal from divoting (1). Historically the most troublesome weed in CBG has been annual bluegrass (ABG) (12,13). This winter-annual is considered undesirable because of the unattractive yellow-green color and profuse seedhead production during the spring which disrupts turfgrass appearance and affects use (1).…”
mentioning
confidence: 99%
“…Creeping bentgrass (CBG) is the cool-season turfgrass species of choice for golf course fairways and tees throughout the cool-humid region because it tolerates close mowing, remains green year-round, and possesses lateral stems that enable it to self-heal from divoting (1). Historically the most troublesome weed in CBG has been annual bluegrass (ABG) (12,13). This winter-annual is considered undesirable because of the unattractive yellow-green color and profuse seedhead production during the spring which disrupts turfgrass appearance and affects use (1).…”
mentioning
confidence: 99%
“…Numerous studies (4,7,8,10,13) have been conducted with DCP A as a preemergence application for control of annual bluegrass (Poa annua L.). Acceptable annual bluegrass control was obtained in Alabama (13) and Virginia (4) but not in Georgia (8,10).…”
mentioning
confidence: 99%
“…Acceptable annual bluegrass control was obtained in Alabama (13) and Virginia (4) but not in Georgia (8,10). Gross (7) reported that DCP A would give good preemergence annual bluegrass control if applications were made to coincide with seed germination. However, in Georgia (8), annual bluegrass control was poor when DCPA treatments were applied during a period from July to October in each of 3 years at Griffin and I of 2 years at Lawrenceville (8).…”
mentioning
confidence: 99%
“…The tolerance of seedling Kentucky bluegrass to linuron [3-(3,4-dichlorophenyl) Annual bluegrass is a major weed problem on golfcourses, particularly in areas subject to excessive irrigation, wear and/or soil compaction (Juska and Hanson 1967;Perkins 1974). Chemical control has been attempted but selectivity has generally not been acceptable (Engel and Callahan 1967;Goss 1964 Kentucky bluegrass and a stand of Victa Kentucky bluegrass were tolerant to linuron (G) at rates from 3.4 to 6.7 kglha (Table 2).…”
mentioning
confidence: 99%